2012
DOI: 10.1118/1.3685586
|View full text |Cite
|
Sign up to set email alerts
|

Experimental assessments of intrafractional prostate motion on sequential and simultaneous boost to a dominant intraprostatic lesion

Abstract: The impact of intrafractional prostate motion on dose delivery is sensitive to different motion patterns but not to different delivery techniques. Dose escalation to DIL using either sequential or simultaneous boost plans with 7 mm PTV margin is achievable in the presence of intrafractional prostate motion, even if the severe motion comprised 8.6% (3 out of the 35) treatment fractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…First, we used T2WI and DWI to determine IPLs but did not use PET images. To determine IPLs, some studies have used 11 C choline PET [28][29][30][31] or prostate-specific membrane antigen-targeted PET [32] images. However, a combination of T2WI and DWI was used in PI-RADS version 2 to improve the detectability of prostate cancer [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…First, we used T2WI and DWI to determine IPLs but did not use PET images. To determine IPLs, some studies have used 11 C choline PET [28][29][30][31] or prostate-specific membrane antigen-targeted PET [32] images. However, a combination of T2WI and DWI was used in PI-RADS version 2 to improve the detectability of prostate cancer [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous experimental investigation, we showed that DIL boosts can be safely achieved in the presence of intrafraction motion when using a PTV margin of 7 mm. 31 More recent studies have shown that tracking intraprostatic fiducial markers and accounting for 6 degrees of freedom in prostate motion can reliably monitor prostate position during delivery with an accuracy of 0.2 AE 1.3 and 0.1 AE 0.5 mm for rotation and translation, respectively. 32 Fiducial tracking has been associated with lower toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In a planning study with and without simulated intrafraction motion [10] a safety margin of 7 mm was found to make both sequential or simultaneous boosts feasible. This is in agreement with our simulation showing that already a safety margin of 5 mm will yield 97% of the dose to 100% of the IPL volume.…”
Section: Discussionmentioning
confidence: 99%
“…A simultaneous integrated boost (SIB) to the dominant IPL is a strategy to fight such recurrences [14]. Toxicity seems to be less of a problem [58], however it has been suggested that intrafraction motion requires either intrafraction motion tracking in case of small margins [9] or substantial margins [10].…”
Section: Introductionmentioning
confidence: 99%